Clinical uremic syndrome scores and mortality in peritoneal dialysis: a multi-center retrospective study - Xianfeng Wu; Wenjun Lin; Jinyuan Zhao; Na Tian; Qingdong Xu; Yueqiang Wen; Xiaojiang Zhan; Fenfen Peng; Xiaoyang Wang; Ning Su; Xiaoran Feng; Niansong Wang; et al. (Scientific Reports)
Abstract No study has comprehensively investigated the association between comorbidities, uremic-specific complications (collectively defined as clinical uremic syndrome [CUS]), and mortality in peritoneal dialysis (PD) patients. We conducted a retrospective cohort study including 4,424 incident PD patients from seven centers in China. Comorbidities and complications were each assigned one point: cardiovascular disease, peripheral vascular disease, cerebrovascular disease, diabetes mellitus, hypertension, hyperlipidemia, malnutrition, and anemia. Patients aged 50 years or older received additional points. The total score (CUS score) was calculated to evaluate its association with mortality in PD patients. Over 18,898.4 person-years of follow-up, 1,208 patients (27.3%) died. The median CUS score was 3 (interquartile range [IQR] 2–5; range, 1–11). A nonlinear association between CUS scores and all-cause mortality was observed (nonlinear, p = 0.006). A pre-1point increase in the CUS score was associated with a 1.35-fold increase in the risk of all-cause mortality (95% confidence interval [CI], 1.31–1.39). Compared with patients with CUS scores ≤ 3, those with scores > 3 had a 2.81-fold higher risk of mortality (95% CI, 2.47–3.21). Higher CUS scores were significantly associated with increased all-cause mortality risk in PD patients, particularly those with scores > 3.